Hubungan Kadar Hemoglobin Ibu Hamil Trimester III Dengan Berat Lahir Bayi Di Wilayah Kerja Puskesmas Koto Baru - Kencana, Dwike Cenderamata; Purwati, Rati; Hafiza, Hafiza (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Low maternal hemoglobin levels below 11 g/dl during the third trimester can result in a lack of oxygen to the placental tissue and will interfere with fetal growth, and can increase the risk of premature delivery and low birth weight babies (Nair et al., 2018). The purpose of this study was to determine the relationship between hemoglobin levels in the third trimester of pregnant women and birth weight in the working area of ​​the Koto Baru Health Center. This type of research is survey analitik with a cross sectional approach. sampling using sampling technique with Consecutive sampling. The statistical test used is the chi-square test. The sample in this study were third trimester pregnant women who would give birth in the Koto Padang district as many as 40 respondents. From the test results, it was found that there was a significant p-value of 0.00, meaning that there was a significant relationship between the hemoglobin levels of TM III pregnant women and the baby's birth weight. Suggestions for respondents to pay attention to nutrition during pregnancy and routinely go to the nearest health service, monitor the mother's hemoglobin level during pregnancy so that they can find out the development of the baby in the mother's womb.